Cost-utility analysis of empagliflozin in heart failure patients with reduced and preserved ejection fraction in China - Tang, Yi; Sang, Haiqiang (Frontiers in Pharmacology, 2022)
Objective: EMPEROR-Reduced and EMPEROR-Preserved study showed the benefits on empagliflozin along with a reduction in cardiovascular death or hospitalization for heart failure. Our aim was to evaluate the economics and effectiveness of adding empagliflozin to standard therapy in heart failure with reduced ejection fraction (HFrEF) and heart failure with preserved ejection fraction (HFpEF) in China. Methods: A multistate Markov model was constructed to yield clinical and economic outcomes of adding empagliflozin to standard therapy for 65-year-old patients with HFrEF and HFpEF. A cost-utility analysis was conducted mostly derived from the EMPEROR-Reduced study, EMPEROR-Preserved study and national statistical database. All costs and outcomes were discounted at a rate of 5% per annum. The primary outcome were total and incremental costs and quality-adjusted life years (QALYs) and the incremental cost-effectiveness ratio (ICER). Sensitivity analyses were performed. Results: In the HFrEF population, the 10-year incremental cost was $827.52 and the 10-year incremental QALYs was 0.15 QALYs, resulting in an ICER of 5,612.06 $/QALY, which was below the WTP of $12,652.5/QALY. In the HFpEF population, compared with the control group, the incremental cost was $8,132.12 and the incremental QALYs of 0.11 QALYs, yielding an ICER of 11,312.65 $/QALY, which was also below the WTP of $12,652.5/QALY. In HFrEF and HFpEF population, the results of one way sensitivity analysis showed the risk of cardiovascular death in both group was the most influential parameter. In HFrEF population, a probabilistic sensitivity analysis(PSA) results revealed that when the WTP threshold was $12,652.5 /QALY and $37,957.5/QALY, the probability of being cost‑effective for the add‑on empagliflozin was 59.4% and 72.6% respectively. In HFpEF population, PSA results revealed that the probability of being cost‑effective for the add‑on empagliflozin was 53.1% and 72.2% respectively. Conclusion: Considering the WTP threshold was $12,652.5/QALY, adding empagliflozin to standard therapy was proved to be a little more cost-effective option for the treatment of HFrEF and HFpEF from a China healthcare system perspective, which promoted the rational use of empagliflozin for HF.